Comunidad de aprendizaje para promover inversión privada en agrícultura climaticamente adaptada: Presentación en Regional Forum Building resilience in coffee dependent communities - Managua, Nicaragua - Lundy, Mark M. (2016)
Road map to incentivize private sector investment in climate resilience in coffee value chains.